Employment Regulation : Rules for Hiring and Termination - Betcherman, Gordon (World Bank, Washington, DC, 2012)
Employment protection - the set of rules governing hiring and terminating employees - is a key feature of any country's labor market. What types of contracts will be permitted between employers and employees? Under what conditions can the relationship be terminated? What are the requirements for providing advance notice? What are the obligations of the employer regarding severance or termination payments? These are important questions for policy-makers in addressing the trade-offs between labor market flexibility and the economic security of employed workers. A mix of cultural norms, collective bargaining, and legislation determines employment protection practices in any country. This primer note focuses on the statutory regulations affecting employment protection. It provides a basic overview of the policy options and a summary of what is known about their impacts on workers and on the labor market. It also addresses the institutional and political aspects of employment protection.